Padronização da técnica de aglutinação em látex para o diagnóstico indireto da leptospirose: preparo do antígeno recombinante - Araújo, Bruno Vinicios Silva de (Universidade Federal Rural do Semi-Árido, 2019)
Leptospirosis is seen as the most widespread anthropozoonosis in the world. According to the serological classification, the species Leptospira interrogans includes the pathogenic serovars mostly involved in infections that affect man and animals, being LipL32 the most abundant and highly immunogenic transmembrane protein. The use of lipoproteins, such as LipL32, may represent a lower cost, higher safety and specific alternative for the development of serological diagnostic tests. Thus, the objective was to contribute to the development of a rapid diagnostic point of care test, easily to read and interpret that can diagnose human and animal leptospirosis in minutes at any stage of infection. Genomic DNA extracted from standard strains of 19 pathogenic leptospires (serovar Australis, Autumnalis, Bataviae, Bratislava, Canicola, Castellonis, Copenhagen Panama, Pomona, Sejroe, Tarassovi, Wolfii). The oligonucleotides primers used for amplification of this gene have been validated in published studies, according to Seixas et al. (2007) and Amutha et al. (2007). PCR amplification products were submitted to 1% agarose gel electrophoresis in Tris-Acetate-EDTA (TAE) buffer, using ethidium bromide (0.5mg / mL) as DNA evidencing dye. The primers had, at their 5 'ends, restriction sites for the EcoR I and Kpn I enzymes, to allow insertion in the right direction into the recombinant plasmid. The recombinant vector used in this study had been previously constructed, pAE / lipL32 (SEIXAS, et al., 2007). The strains used were E. coli XL1-Blue, BL21 (DE3) PLys and E. coli BL21 Star ™ (DE3) strains. E. coli XL1-Blue was used for cloning and BL21 (DE3) PLys and E. coli BL21 Star ™ (DE3) were used for expression of recombinant proteins. CaCl2 competent bacteria preparation, E. coli XL1-Blue bacterial transformation, transformed cell culture, plasmid extraction, expression cell transformation, inoculum growth and isopropyl-β-D-thiogalactopyranoside expression induction were performed. Recombinant protein extraction by sonicator cell lysis and LipL32 protein analysis by SDS-PAGE polyacrylamide gel electrophoresis. Of the 19 samples submitted to PCR directed to lipoprotein gene LipL32, all were positive, resulting in amplification of a region of 756 bp and 771 bp as expected given that LipL32 is encoded by a conserved gene among the pathogenic Leptospira species. After selection of white colony forming units (CFUs), the presence of LipL32 gene was detected by PCR amplification. Evidence of high transformation rate in E. coli XL1-Blue strain and successful cloning of Leptospira LipL32 gene for heterologous expression of the corresponding peptide. Samples from the expression protocol using the E. coli BL21 (DE3) PLys bacterial strain were sonicated and the aliquots used to verify the time the protein was expressed in the highest concentration by the bacterium by electrophoresis on an SDS-PAGE. LipL32 protein was successfully expressed however adjustments to improve protein extraction level are needed. The bacterial strain E. coli BL21 Star ™ (DE3) showed no transformation rate and consequently no heterologous protein expression.
Artigo Acadêmico
Keywords: Leptospira; LipL32; Diagnóstico; Leptospira; LipL32; Diagnosis; CIENCIAS AGRARIAS::MEDICINA VETERINARIA